2021
DOI: 10.1177/13567667211063206
|View full text |Cite
|
Sign up to set email alerts
|

Rio 2016 Olympic Games: Brand and the reciprocal effects of touristic destinations

Abstract: This study analyzes the effect of Brazil's national tourism brand on the image of Rio de Janeiro as the host city of the 2016 Olympic Games, and the reciprocal effect of Rio de Janeiro on Brazil, considering both as tourist destinations. A quantitative study was employed using structured questionnaires, with a sample of foreign respondents ( n = 340) and a simultaneous equation method. A positive reciprocal effect was found. In general, the perception of a country as a tourist destination influences destinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 78 publications
(118 reference statements)
0
12
0
Order By: Relevance
“…The influences of event image in those places have been investigated, but the relations between the two places, as the influence of the host city in the nation image is a new approach. This was partially investigated in Ferreira et al (2022), it was observed that there is a greater influence of the host city in the country than the opposite, which strengthens the thesis of the impact of the event itself, but also of the host city.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…The influences of event image in those places have been investigated, but the relations between the two places, as the influence of the host city in the nation image is a new approach. This was partially investigated in Ferreira et al (2022), it was observed that there is a greater influence of the host city in the country than the opposite, which strengthens the thesis of the impact of the event itself, but also of the host city.…”
Section: Introductionmentioning
confidence: 76%
“…Considering that context, the city impacts of hosting the event can overflow for the nation branding, especially for the image. Rio's overall city image as a host of Olympics had influenced on Brazil's overall image as a tourist destination (Ferreira et al, 2022), so the Rio image dimensions can affect Brazil's overall destination image. Thus, the first hypothesis is:…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the primary stage, the idea of educating people through sports resulted in a narrative form with a focus on recording, supplemented with empathy and experience (Baker, 1998 ). On this basis, scholars have carried out academic research on the theme of sports, successively made explorations on the screen culture related to issues of nation, country, and esthetics, and officially launched the integration of sports, short video, and films (Barber, 2014 ; Rodesiler, 2014 ; Ferreira et al, 2022 ). As an integral part of the film family, sports film has many fans, and its research has attracted extensive attention from experts in various fields of academia.…”
Section: Study 1: Literature Review and Research Questionsmentioning
confidence: 99%